Penentuan Kadar Gula Reduksi Pada Tebu (Saccharum officinarum) yang Tumbuh di Daerah Nimbokrang Kabupaten Jayapura - Jenmau, Irja Sepriyanto; Suaka, Irwandi Yogo; Bwefar, Marsia Isa (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Research has been conducted at the Chemistry Education Laboratory on the determination of reduced sugar levels in sugarcane (Saccharum Officinarum) originating from Nimbokrang, Jayapura Regency through an iodometric titration process. The purpose of this study is to determine the reduced sugar content in sugarcane (Saccharum officinarum) originating from Nimbokrang, Jayapura Regency. By knowing the reduced sugar content in sugarcane, people can process sugarcane not only as yard plants, but can be used as more effective plants. This research is experimental by describing the data of research results and literature studies. Sugarcane juice samples were then analyzed using the Luff-Schoorl method. The results of the analysis obtained the reduced sugar content in sugarcane from Nimbokrang, Jayapura Regency, which was 21.8817 g in 100 grams (21.8817 %) of sugarcane water. With a fairly high reduced sugar content, sugarcane juice can be used as a complement to alternative energy sources.